2018
DOI: 10.1111/adb.12649
|View full text |Cite
|
Sign up to set email alerts
|

Social deficits following embryonic ethanol exposure arise in post‐larval zebrafish

Abstract: Prenatal alcohol exposure is the leading cause of birth defects, collectively termed fetal alcohol spectrum disorders (FASD). In the United States and Canada, 1 in 100 children will be born with FASD. Some of the most commonly debilitating defects of FASD are in social behavior. Zebrafish are highly social animals, and embryonic ethanol exposure from 24 to 26 hours post-fertilization disrupts this social (shoaling) response in adult zebrafish. Recent findings have suggested that social behaviors are present in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Redesigning our protocol to test different cues instead of stripes and extending the alcohol association period (more than only one day) will be needed to clarify the specific reason for such a difference. Similar inconsistent results between various ages were observed in the study by Fernandes and colleagues (Fernandes et al., 2019), in which the authors observed embryonic alcohol exposure disruptive shoaling response in adults but not in larvae zebrafish. The authors refer to neurocircuitry differences between larval and adult social behaviors, which can also be a plausible explanation for the results obtained in our study on CPP.…”
Section: Discussionsupporting
confidence: 79%
“…Redesigning our protocol to test different cues instead of stripes and extending the alcohol association period (more than only one day) will be needed to clarify the specific reason for such a difference. Similar inconsistent results between various ages were observed in the study by Fernandes and colleagues (Fernandes et al., 2019), in which the authors observed embryonic alcohol exposure disruptive shoaling response in adults but not in larvae zebrafish. The authors refer to neurocircuitry differences between larval and adult social behaviors, which can also be a plausible explanation for the results obtained in our study on CPP.…”
Section: Discussionsupporting
confidence: 79%
“…EAE had no detectable impact on food consumption in adult males, suggesting that it is an unlikely mechanism for increased adiposity ( Figure 4B). Multiple studies have demonstrated that EAE affects zebrafish swimming behaviors (35)(36)(37)(38). To determine whether reduced locomotion was present in adults after EAE, we assessed activity level (35,(39)(40)(41)(42)(43)(44).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the chorion, which surrounds the early zebrafish embryo, appears freely permeable for ethanol. Zebrafish embryonic ethanol levels reach approximately 25–35% of the embryo medium level ( Blader and Strahle, 1998 ; Ali et al, 2011 ; Fernandes et al, 2019 ). In zebrafish, both short-term and chronic ethanol exposure increase the incidence of craniofacial malformations.…”
Section: Alcoholmentioning
confidence: 99%